Regulasi dan Penegakan Hukum Lingkungan dalam Menangani Kebakaran Hutan Berdasarkan Undang-Undang Nomor 32 Tahun 2009 - Harvelian, Agnes; Ashraf, Muhammad; Kartika, Tantri (PT Elaborium Elevasi Indonesia, 2023)
The importance of maintaining environmental balance and dealing with complex issues such as forest fires in Indonesia requires attention to the relevant legal aspects. The concept of the environment involves the human area and the accumulation of its activities, with forests playing a central role in maintaining ecosystems and providing benefits for society. Law Number 32 of 2009 concerning Environmental Protection and Management is a strong legal basis for dealing with this problem. This research method applies a normative approach and literature study to analyze legal aspects related to forest fires. Within this framework, the statutory approach is used to collect all laws and regulations that are relevant to the legal issues being studied, especially in the context of enforcing criminal law against forest fires as an environmental crime. The results reveal the importance of effective law enforcement in the environmental context, which is regulated by Article 98 of Law Number 32 of 2009. This article outlines criminal sanctions for those who violate air, water, or environmental damage criteria.